Can pupillometry distinguish accurate from inaccurate familiarity?. (5th May 2021) - Gomes, Carlos A.; Montaldi, Daniela; Mayes, Andrew
Abstract: Pupillometry, the measurement of pupil diameter, has become increasingly popular as a tool to investigate human memory. It has long been accepted that the pupil is able to distinguish familiar from completely novel items, a phenomenon known as "pupil old/new effect". Surprisingly, most pupillometric studies on the pupil old/new effect tend to disregard the possibility that the pupillary response to familiarity memory may not be entirely exclusive. Here, we investigated whether the pupillary response to old items correctly judged familiar (hits; accurate familiarity) can be differentiated from the pupillary response to new items wrongly judged familiar (false alarms; inaccurate familiarity). We found no evidence that the two processes could be isolated, as both accurate and inaccurate familiarity showed nearly identical mean and across‐time pupillary responses. However, both familiarity hits and false alarms showed pupillary responses unequivocally distinct from those observed during either recollection or novelty detection, which suggests that the pupil measure of familiarity hits and/or false alarms was sufficiently sensitive. The pupillary response to false alarms may have been partially driven by perceptual fluency, since novel objects incorrectly judged to be old (i.e., false alarms) showed a higher degree of similarity to studied images than items correctly judged as novel (i.e., correct rejections). Thus, our results suggest that pupil dilation may not be able to distinguish accurate from inaccurate familiarity using standard recognition memory paradigms, and they also suggest that the pupillary response during familiarity feelings may also partly reflect perceptual fluency. Abstract : Pupil dilation to familiarity hits is often used to index accurate familiarity memory. However, it might also reflect priming or fluency effects. We compared the pupillary response between familiarity hits and false alarms. The results showed that pupil dilation does not distinguish accurate from inaccurate familiarity during recognition memory judgments. Thus, pupil dilation to familiarity hits may not always indicate accurate familiarity and could instead reflect a shared process with false alarms, such as fluency.